Xylose recovery and bioethanol production from sugarcane bagasse pretreated by mild two-stage ultrasonic assisted dilute acid. (February 2022) - Chen, Sheng-Jie; Chen, Xiong; Zhu, Ming-Jun
Graphical abstract: Highlights: Treating bagasse (SCB) by 2-stage ultrasonic assisted dilute H2 SO4 (TUDA). Lignin and hemicellulose can be efficiently removed by TUDA pretreatment at 90℃. Optimal ethanol fermentation efficiency at cellulase 10 FPU/g SCB and 30% SCB. Recovering xylose effectively from pretreated liquid by bagasse-derived biochar. Full utilization was achieved for SCB from solid residue to pretreatment liquid. Abstract: Pretreatment can improve biomass biodegradability. Here, a novel sugarcane bagasse (SCB) pretreatment process based on two-stage ultrasonic assisted dilute H2 SO4 (TUDA) under mild conditions was reported. After optimization, the pretreatment was shown to significantly degrade hemicellulose (92.40%) and remove lignin (57.41%) of SCB, leading to reduction of inhibitors and an ethanol fermentation efficiency of 93.37% by SSCF under cellulase 10 FPU/g SCB and 30% pretreated SCB loading. Physical characterization revealed that two-stage ultrasonic could better disrupt SCB than traditional ultrasonic by amplifying the collapse effect and synergistically promoting lignin removal through dilute H2 SO4 . Furthermore, xylose was also effectively recovered from pretreatment supernatant by biochar derived from bagasse. This study established a simple and efficient pretreatment process for high value-added recycling of SCB from solid residue to pretreatment liquid.